Hooke's Law

# Derivation

## Equation of Motion from Cons of Energy

In the previous chapter Forest_UCM_Energy_Line1D, we saw how the equations of motion could from the requirement that Energy be conserved.

- [math]E = T + U[/math]
- [math] T = E - U[/math]
- [math] \frac{1}{2} m v^2 = E- U[/math]

in 1-D

- [math] \dot {x}^2 = \frac{2}{m} \left ( E-U(x) \right )[/math]
- [math] \dot {x}^2= \frac{2}{m} \left ( E-U(x) \right )[/math]
- [math] \dot {x}= \sqrt{\frac{2}{m} \left ( E-U(x) \right )}[/math]
- [math] \frac{dx}{dt}= \sqrt{\frac{2}{m} \left ( E-U(x) \right )}[/math]
- [math] \frac{dx}{ \sqrt{\frac{2}{m} \left ( E-U(x) \right )}}=dt[/math]
- [math] \sqrt{\frac{m}{2}} \int \frac{dx}{ \sqrt{\left ( E-U(x) \right )}}=\int dt[/math]

Let consider the case where an object is oscillating about a point of stability [math](x_0)[/math]

A Taylor expansion of the Potential function U(x) about the equilibrium point [math](x_0)[/math] is

- [math]U(x) = U(x_0) \; + \; \left . \frac{\partial U}{\partial x} \right |_{x=x_0} (x-x_0) \; + \; \frac{1}{2!}\left . \frac{\partial^2 U}{\partial x^2} \right |_{x=x_0} (x-x_0)^2 \; + \; \frac{1}{3!}\left . \frac{\partial^3 U}{\partial x^3} \right |_{x=x_0} (x-x_0)^3 \; + \dots [/math]

Further consider the case the the potential is symmetric about the equilibrium point [math](x_0)[/math]

at the equilibrium point

- [math]\left . \frac{\partial U}{\partial x} \right |_{x=x_0} = 0 [/math]: Force = 0 at equilibrium

in order to have stable equilibrium

- [math]\left . \frac{\partial^{2} U}{\partial x^{2}} \right |_{x=x_0} \gt 0 [/math]: stable equilibirium

also the odd (2n-1) terms must be zero in order to have stable equilibrium for a symmetric potential (the potential needs to be a max at the end points of the motion).

- [math]\left . \frac{\partial^{2n-1} U}{\partial x^{2n-1}} \right |_{x=x_0} = 0 [/math]:

and the leading term is just a constant which can be dropped by redefining the zero point of the potential

- [math]U(x_0) = 0[/math]

This leaves us with

- [math]U(x) = \frac{1}{2!}\left . \frac{\partial^2 U}{\partial x^2} \right |_{x=x_0} (x-x_0)^2 \; + \; \frac{1}{4!}\left . \frac{\partial^4 U}{\partial x^4} \right |_{x=x_0} (x-x_0)^4 \; + \dots [/math]

if we make the following definitions

- [math] \left . \frac{\partial^2 U}{\partial x^2} \right |_{x=x_0} \; = k [/math]

- [math]U(x) = \frac{1}{6} \left . \frac{\partial^4 U}{\partial x^4} \right |_{x=x_0} \; = \epsilon [/math]

and that the equilibrium point is located at the orgin

- [math]x_0 = 0[/math]

Then

- [math]U(x) = \frac{1}{2}kx^2 \; + \; \frac{1}{4}\epsilon x^4 \; + \dots [/math]

Since we began this derivation with the assumption that energy was conserved then the force must be conservative such that

[math]: \vec F = - \vec \nabla U[/math]

or this 1-D force can be written as

[math]F = - \frac{\partial }{\partial x} U (x) = - kx - \epsilon x^3 - \dots[/math]

# Interpretation (Hooke's law)

Returning back to the conservation of energy equation

- [math] E = T + U = \frac{m}{2} \dot {x}^2 + \frac{1}{2}kx^2 \; + \; \frac{1}{4}\epsilon x^4 \; + \dots [/math]

Lets consider only the first term in the expansion of the potential U(x)

- [math] E = \frac{m}{2} \dot {x}^2 + \frac{1}{2}kx^2 [/math]
- [math] \frac{dE}{dt} = \frac{m}{2} 2 \dot {x} \ddot x + \frac{1}{2}k2 x \dot x = 0 [/math] energy is constant with time
- [math] m\ddot x =-kx [/math] energy is constant with time

A Force exerted by a spring is proportional to the spring displacement from equilibrium and is directed towards restoring the equilibrium condition. (a linear restoring force).

In 1-D this force may be written as

- [math]F = - kx[/math]

While the above was derived from the assumption of conservation of energy we can apply our two tests for conservative forces as a double check:

1.) The force only depends on position.

2.) The work done is independent of path ( [math]\vec \nabla \times \vec F = 0[/math] in 1-D and 3-D)

Forest_UCM_Osc#Hooke.27s_Law